Socıal Capıtal And Economıc Behavıor Of Farmers Case Study of Pajale UPSUS Participantin Waihatu Village - Leunard Onisivorus Kakisina; Paulus. M. Puttileihalat (Cita Konsultindo Research Center, 2024)
This study analyzes the relationship between social capital which influences the economic behavior of farmers in producing and increasing the income of pajale farmers This research was conducted in Waihatu village, West Kairatu District, West Seram Regency, and lasted for two months from November – December 2023, which was a participant in the UPSUS pajale program. Focuses on the role of social capital in influencing farmers' economic behavior to produce and increase income. This research uses a qualitative research design using case studies and in-depth interviews, observations, and document research. The results of the research show that the elements of social capital of trust, cohesiveness, altruism, mutual cooperation and networking influence economic behavior, namely the production of pajale plants, the element of trust increases the adoption of technology using superior seeds, the element of cohesiveness can increase mutual interest or pleasure between fellow members in the same group or group. Between groups, the element of altruism can increase mutual help among group members voluntarily without expecting anything in return. the mutual cooperation element can increase cooperation between fellow group members, and the networking element can increase cooperation between farmers and traders which has existed for a long time in relation to the selling price of pajale. The novelty in this research is that the social capital and economic behavior of farmers is a profitable collaboration between farmers.